1985
DOI: 10.1177/019459988509300508
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Role of IgE‐Mediated Hypersensitivity in Recurrent Otitis Media with Effusion

Abstract: One hundred young patients with recurrent otitis media with effusion (OME) were evaluated for IgE-mediated hypersensitivity by critical analysis of history, physical findings, skin testing for selected antigen, laboratory determination of total IgE, and radioallergosorbent testing (RAST) for six inhalant and two food allergens. The patients could be divided into allergic rhinitis and nonallergic groups. Allergic rhinitis patients had higher total IgE in their serum, and middle ear effusion (MEE). IgE was eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 13 publications
3
44
1
1
Order By: Relevance
“…Our epidemiologic data support the existence of a relationship between OME and atopic disease. In fact, of 2097 subjects of paediatric population considered ranging from 5 to 14 years of age, atopy was evidenced by means of routine skin testing in 15.3% (321 subjects); of these 90 had OME with a percentage of 28.03% according to Becker et al [14] who suggested an allergic genesis of recurrent OME in about 20-30% of patients and according to Bernstein et al who detected an allergic basis in 35% of patients [15]. The percentage of atopy in overall 143 children suffered from OME, was 62.9% (90 children) on the basis of positive skin tests; these results seem to identify a strong correlation of atopy with OME (or = 12.67; r = 0.9971).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our epidemiologic data support the existence of a relationship between OME and atopic disease. In fact, of 2097 subjects of paediatric population considered ranging from 5 to 14 years of age, atopy was evidenced by means of routine skin testing in 15.3% (321 subjects); of these 90 had OME with a percentage of 28.03% according to Becker et al [14] who suggested an allergic genesis of recurrent OME in about 20-30% of patients and according to Bernstein et al who detected an allergic basis in 35% of patients [15]. The percentage of atopy in overall 143 children suffered from OME, was 62.9% (90 children) on the basis of positive skin tests; these results seem to identify a strong correlation of atopy with OME (or = 12.67; r = 0.9971).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, OME is a topic for concern, which requires prevention and treatment; in particular the recognition of all risk factors for OME represents certainly the crucial value to the physicians in the clinical management of patients. Frequent discussion topics are the associations with demographic factors, socioeconomic class, passive smoking, bottle-feeding, allergy, sex, tonsillitis, acute otitis media (AOM) and family history of otitis media [6,8,[14][15][16][17][18][19][20]. Even if risk indicators for OME have been widely studied in western countries, modern literature regarding risk factors for OME in Sicily children is however lacking.…”
Section: Introductionmentioning
confidence: 99%
“…There was increased IgE in the middle ear effusion in 14 out of 32 children with allergic rhinitis, compared with two out of 45 children considered to be non-allergic. 7 This finding, however, only allows the inference that the allergic have more IgE than the non-allergic, and that this IgE also affects middle ear effusion.…”
Section: Resultsmentioning
confidence: 99%
“…However, it would also rely on future studies including clinical research or animal models to find out the mechanism, such as through endocochlear inflammation, if at all. The role of allergy in the etiopathogenesis of sudden hearing loss has been uncovered clinically and firstly among children patients [23,24]. The IgE levels were found to be higher among patients with hearing loss, compared to healthy subjects.…”
Section: Main Findingsmentioning
confidence: 99%